Pengaruh Senam Dismenore Terhadap Tingkat Nyeri Haid Pada Remaja Putri Di SMK Negeri 1 Kota Gorontalo - Retni, Ani; Harismayanti; Modjo, Dewi; Muksin, Marlin (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: Dysmenorhea is a physical disorder in menstruating women in the form of abdominal pain/cramps. The cramps are mainly felt in the lower abdominal area radiating to the back or inner surface of the thigh. The purpose of the study was to determine the effect od dysmenorhea gymnastics on the level of menstrual pain in adolescent girls. Methods: The research method uses experimental research design (Quasi Experiment) pre-post test with one group design. The sample of this study were 15 female adolescent respondents at SMK Negeri 1 Gorontalo City. Results: Research results can be seen that there is decrease in the level of pain before and after dysmenorhea gymnastics shows that there is an effect of dysmenorhea gymnastics on reducing menstrual pain shown based on paired sample t-test with a p-value=0.000 which means <α 0.05. Conclusion: The conclusion is that there is an effect on reducing the level of menstrual pain in adolescent girls before and after being given dysmenorhea exercises.